Discovery and Characterization of an Atypical Crustin Antimicrobial Peptide from Pollicipes pollicipes - Wei Zhang; Liumi Wei; Pengyu Chen; Biao Ning; Junjian Wang; Peng He; Chenjing Shang; Dahui Yu (Marine Drugs)
Crustins are a family of antimicrobial peptides (AMPs) that play a pivotal role in the innate immune system of crustaceans. The discovery of novel AMPs from natural sources is crucial for expanding our current database of these peptides. Here, we identified and characterized a novel member of the crustin family, named PpCrus-SWD1, derived from Pollicipes pollicipes. PpCrus-SWD1 consists of 138 amino acids and contains eight cysteine residues that form a conserved ‘four-disulfide core’ structure. Our recombinant PpCrus-SWD1 (rPpCrus-SWD1) exhibited potent inhibitory activity against three Gram-positive bacteria (Staphylococcus aureus, Bacillus sp. T2, and Streptococcus agalactiae) and six Gram-negative bacteria (Aeromonas hydrophila, Escherichia coli, Vibrio anguillarum, Vibrio alginolyticus, Vibrio parahemolyticus, and Acinetobacter sp. L3), with minimum inhibitory concentrations ranging from 16 to 64 μM. Furthermore, rPpCrus-SWD1 demonstrated binding affinity towards both bacteria and pathogen-associated molecular patterns (PAMPs), and damaged bacterial barrier. Additionally, it effectively inhibited alkaline protease activity in S. aureus and V. alginolyticus strains. These findings highlight the potential utility of this newly discovered crustin as an effective alternative to antibiotics.